Xanthine oxidase inhibitory activity of Pandanus amaryllifolius roxb. / Nur Afira Ahmad Shukor - Nur Afira , Ahmad Shukor (2017)
Xanthine oxidase (XO) is a pivotal enzyme in purine metabolism. As the end product, overproduction of uric acid may lead to hyperuricemia and gout disease. This research was conducted to assess the antioxidant potential and xanthine oxidase inhibitory activity of Pandanus amaryllifolius Roxb. P. amaryllifolius was extracted with hexane, petroleum ether, chloroform, methanol and distilled water, where the crude extracts were named as PA-H, PA-PE, PA-C, PA-M, and PA-W respectively. The TLC result showed the presence of terpenoids in all of the extracts. The total phenolic and flavonoid contents were conducted in P. amaryllifolius extracts. PA-W showed the highest TPC with 12.88 ± 0.43 mg GAE/g of dry extract whereas PA-PE showed the highest TFC with 15.02 ± 0.58 mg QE/g of dry extract. Antioxidant activities were performed on P. amaryllifolius extracts and PA-W generally exhibited the highest activity. In DPPH, metal chelating, and hydrogen peroxide assay, all extracts displayed low scavenging activity. However, each extract possessed steady increase in inhibition activity within their concentration range. PA-W showed the highest activity in DPPH (>240 g/mL), metal chelating (>160 g/mL), and hydrogen peroxide assay (>320 g/mL). PA-M showed the highest activity in FRAP assay (64.39 ± 2.79 mmol Fe2+/g of dry extract). TPC revealed positive significant correlation with DPPH (r = 0.972, P<0.01), FRAP (r = 0.964, P<0.01), and hydrogen peroxide assay (r = 0.898, P<0.05), but no correlation with metal chelating assay (r = 0.382) and in vitro XO inhibitory activity (r = 0.809). TFC showed negative correlation with all assays. In in vitro XO inhibitory activity, PA-W displayed the highest activity (>100 g/mL). In in vivo XO inhibitory activity, acute toxicity test of PA-W tested at 2 g/kg body weight showed no signs of toxicity and mortality after 14 days. The treatment with PA-W showed significant (P<0.001) decrease in serum uric acid level and XO activity. At the dose of 1000 mg/kg body weight and 500 mg/kg body weight, the serum uric acid level were 2.55 ± 2.23 mg/dL and 6.08 ± 1.00 mg/dL, whereas the XO activity were 3.84 ± 0.68 mu/mL and 6.35 ± 0.87 mu/mL, in hyperuricemic rats. Allopurinol standard exhibited serum uric acid level and XO activity of 1.72 ± 1.01 mg/dL and 1.06 ± 0.21 mu/mL respectively. Thus, the results of this finding support the use of P. amaryllifolius in reducing uric acid for the treatment of hyperuricemia and rheumatoid arthritis.